Feed Forage and Nutrition Value at Altitudes during the Dry Season in the West Java - Rochana, Ana; Indriani, Nyimas Popi; Ayuningsih, Budi; Hernaman, Iman; Dhalika, Tidi; Rahmat, Dedi; Suryanah, Sari (ANIMAL PRODUCTION, 2016)
Field grass was a source of ruminant forage, especially for rural farmers in the West Java in different altitude. The aim of this study was to determine the potential of grass during the dry season which included the botanical composition analysis and chemical analysis of nutritional value. The study was conducted from September to November 2015. The method used was a survey method, sampling was multistage sampling. The parameters measured in the study included a botanical composition of the forage, biomass production of feed materials on fresh and dry matter, dry material content, an inorganic material included ash, calcium and phosphorus, protein, crude fiber, extract materials without nitrogen, and crude fat. The results showed that the areas in the West Java were drought in September and October, thus resulting in very limited supply of forage and the productivity of the forages was very low. A botanical composition in the highland area was more complete included grass, legumes and weeds than lowland areas and medium altitude. Forage production in highland areas was higher than in lowland areas and medium altitude. Feed plants in the lowlands had a greater fiber content which was forming energy for plants, and lower crude protein when compared to highland